The peculiarities of economic crisis due to COVID-19 pandemic in a developing country: case of Ukraine - Bohdan Danylyshyn (Problems and Perspectives in Management, 2020)
At the beginning of 2020, the world faced the most frightening threat to the population’s health – COVID-19 pandemic. For this reason, the international institutions, governments of countries and various organizations are forced to use unprecedented restrictive measures in many spheres of activity. As a result, the economies of the countries all over the world are significantly affected and are on the verge of crisis. This paper presents examples of economic consequences of COVID-19 pandemic for different countries of the world and analyzes still few scientific works, which study the influence of pandemic on their economies. The article generalizes the legislative and anti-crisis measures of the Ukrainian Government, as well as the National Bank of Ukraine and other state authorities. It is evidenced that at the end of 2019 and the beginning of 2020, Ukraine witnessed a significant decrease in GDP growth rate, reduction of industrial production and electricity production. The financial indicators also underwent significant losses, particularly the unemployment rate increased as thousands and thousands of labor migrants have returned to Ukraine from European and other countries. The article proves the inconsistency and unprofessionalism of such restrictive and regulatory measures. Finally, the necessity is substantiated to combine the methods of market economy and state regulation. The compulsory steps are offered, which would minimize the losses of the state and its population during this economic crisis.